ChemInform Abstract: In situ Generation of Ammonia for the Copper‐Catalyzed Synthesis of Primary Aminoquinolines. Issue 36 (9th September 2014) - Aillerie, Alexandre; Pellegrini, Sylvain; Bousquet, Till; Pelinski, Lydie
Abstract Formamide acts as ammonia source in the copper‐catalyzed synthesis of primary aminoquinolines.